Comparative study on antibiotic resistance profiles and plasmid presence in water samples focusing inside and outside Dhaka district - Maliha, Sumaiya Tasnim; Zarin, Nusrat Kamrul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.